Pushing away threat to sweet potato - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Joseph Ndunguru of the Plant Protection Division in Mwanza, Tanzania, urges more action in dealing with sweet potato virus disease (SPVD). 'Farmers attempt to control SPVD by selecting disease-free planting material. However, selection is difficult,...